Easy-Z notes mobile application in android application (GPS Feature) - Siti Zulaikha, Azman (2019)
There are some issues when it comes to some mobile applications. It is because the differentiation of users’ desire, for example is the preference of that application. For notes mobile application, the complication found is limitation of its features. The limitations are color theme, type of notes, and notes security. Theme should be in variety color for user to make more choice in creating interesting notes. User needs to create different type of notes. The application should provide more type of notes that not only contain text or list notes. Make it more in variation and locking system needs to be implemented for notes security. When there is no security, the notes created can be easily being deleted automatically when the complication of device occur. The backup and restore features can be applied. The Easy-Z Notes will be developed to overcome any form of constraints and limitations based on user requirements and will be tested whether it fulfilled the requirements. The user requirements gathered will be analyzed to develop better notes mobile application. The development of notes mobile application used some source codes. Same source code can be applied on certain functions that have the same pattern and it becomes easier and reduce time taken in completing the notes application development. Easy-Z Notes application consists of more color themes where user can choose based on their needs. The type of notes implemented are text, draw, to-do-list with GPS, and photo notes. User can create any type of notes. Easy-Z Notes contributes with backup and restore function where user can save the notes data in SD card. The notable for Easy-Z Notes is GPS feature in to-do-list notes where user can easily save the location detected by GPS for user review later without need to search the location whenever user open the to-do-list notes. Time will be reduced and convenient for user in using Easy-Z Notes mobile application.